The development of physiological profiles and identification of training needs in NCAA female collegiate rowers using isoperformance curves. Reply - Fukuda, D. H.; Kendall, K. L.; Smith, A. E.; Stout, J. R. (European Journal of Applied Physiology, 2012)
We appreciate Dr. Jolly`s analysis of our manuscript (Jolly 2012), entitled ``The development of physiological profiles and identification of training needs in NCAA female collegiate rowers using iso-performance curves (Fukuda et al. 2011).`` Their Letter to the Editor poses a number of welldevised considerations that we address in this response, and provides an interesting viewpoint on solely using performance times in the decision-making process by coaches. A primary focus of our manuscript was to address the ability of coaches and trainers to strategically and objectively develop training programs in collegiate rowing athletes with minimal rowing experience. The simplified approach to the critical velocity (CV) concept presented in our manuscript was adopted to increase its applicability in a sport setting. We agree that the use of CV as an aerobic parameter and anaerobic rowing capacity (ARC) as an anaerobic parameter is rather rudimentary, and more appropriate definitions have been proposed (e.g. Jones et al. 2010). Viewing CV as the demarcation point between the heavy- and severe-intensity domains and ARC as the work capacity available above CV would not have drastically changed the outcome of our manuscript. In addition, the partially dependent relationship between modeled CV and ARC is not a complete divergence from the relationship between actual aerobic and anaerobic metabolism. The association between the parameters of the work-time relationship and pulmonary oxygen uptake ( _V O2) kinetics may be used as an example of this concept. Murgatroyd et al. (2011) recently reported an inverse relationship between critical power (CP; a cycling analog of CV) and the fundamental _VO2 time constant, as well as, a positive relationship between W0 (a cycling analog of ARC) and the magnitude of the _V O2 slow component. While these associations do not imply causality, the _V O2 time constant has been related to type I slow-twitch fibers and skeletal muscle mitochondrial density and the _V O2 slow component to the recruitment of type II fast-twitch fibers via muscular fatigue during high-intensity exercise (e.g. Murgatroyd et al. 2011). If coaches or researchers continue to have reservations with the linear relationship provided by CV and ARC from the linear-total distance model, we suggest adopting the recently reported 3-min all-out rowing test, but, as noted by Cheng et al. (2011), similar results would be expected for CV (or CP) with slightly lower values for ARC (W0). Furthermore, the issue of multiple tests may also be addressed using this 3-min test format with CP being estimated as the average power output from the last 30 s and W0 calculated as the power-time integral above CP. The division of athletes based on the mean characteristics of the group used in our manuscript was arbitrary and suggested as a simple means of splitting the sample. Percentiles or accepted norms could easily take their place. We would also suggest caution when comparing training adaptations from swimming with those of rowing, as Dr. Jolly suggests, as the two sports exhibit decidedly different metabolic requirements. Both the determination of adequate group characteristics and appropriate training interventions should be addressed by coaches using their own expertise and personal experience. Our paper does not propose the abandonment of performance times, but rather aims to provide additional tools to aid in the decision-making process of coaches. We advise readers to examine our study sample and note that the athletes are collegiate-level rowers, some of whom have minimal training or competitive experience. For this group, a performance-only approach may leave behind athletes that have yet to develop sport-specific skill sets. Therefore, CV and iso-performance curves may be more appropriate in less experienced, developmental athletes. The use of actual performance tends to be straightforward when dealing with high-level athletes, but there are times when even professional coaches with limited resources may need to adjust their thinking with regard to decision making. The small number of coaches tasked with making decisions regarding Olympic-caliber athletes may simply rely on actual performance, but all coaches may benefit from new methods of evaluating their athletes.